2017
DOI: 10.4067/s0718-95162017005000009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc application strategy on zinc content and productivity of chickpea grown under zinc deficient soils

Abstract: Field experiments were conducted at three locations with Zn deficient soils in southern Ethiopia during 2012 and 2013 cropping seasons to evaluate the effects of Zn fertilization strategies and varietal differences on Zn content and plant performance of chickpea (Cicer arietinum L.). Factorial combinations of three Zn fertilization strategies and five varieties were laid out in a randomized complete block design with three replications in each location and year. A combined analysis of variance was made using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
4
16
0
Order By: Relevance
“…Low yield ascertained under salinity was probably due to the reduction of assimilating production, and the mobilization of photoassimilates resulted in a decrease in harvesting index (Jacob and Francis 2015), pollen viability, and stigmatic receptivity (Khatun and Flowers 1995). However, the present investigation effectively confirmed that zinc forms induced salt tolerance; these results were confirmed by Hidoto et al (2017); Mehrabani et al (2018). The favorable effect of zinc on yield in different plant species may be due to their effects on the increasing activity of carbonic anhydrase and inducing ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) activity that induced CO 2 assimilation and photosynthetic capacity; that is reflected in maximizing dry matter accumulation (Storey 2007;Singh et al 2019).…”
Section: Discussionsupporting
confidence: 60%
“…Low yield ascertained under salinity was probably due to the reduction of assimilating production, and the mobilization of photoassimilates resulted in a decrease in harvesting index (Jacob and Francis 2015), pollen viability, and stigmatic receptivity (Khatun and Flowers 1995). However, the present investigation effectively confirmed that zinc forms induced salt tolerance; these results were confirmed by Hidoto et al (2017); Mehrabani et al (2018). The favorable effect of zinc on yield in different plant species may be due to their effects on the increasing activity of carbonic anhydrase and inducing ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) activity that induced CO 2 assimilation and photosynthetic capacity; that is reflected in maximizing dry matter accumulation (Storey 2007;Singh et al 2019).…”
Section: Discussionsupporting
confidence: 60%
“…Zinc have an important role to activate various hormones like auxin that is needed for proper plant growth (Begum et al 2016). Previous studies also documented that Zn application had a positive effect on grain Zn concentration (Kaya et al 2009;Hidoto et al 2017;Bala et al 2019). In present study, the application of Zn significantly increased the grain Zn concentration in lentil genotypes.…”
Section: Discussionsupporting
confidence: 59%
“…Crop genotypes greatly differ in grain Zn contents as well as the phytate contents (Hussain et al 2011(Hussain et al , 2013. Zinc application and cultivars both influence the yield and nutritional status of crop (Hidoto et al 2017;Manaf et al 2019). However, screening of the existing lentil germplasm for higher grain Zn contents and low phytate contents is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Shivay et al [111] observed a correlation between Zn uptake and the grain yield of chickpeas following foliar application of Zn, and reported that this approach was better than soil application. Similarly, Hidoto et al [112] evaluated the effects of three Zn fertilization strategies on five varieties of chickpeas and observed that foliar application was an effective method for Zn biofortification with a greater accumulation of Zn in grain compared to soil application and seed priming. Foliar application of Zn fertilizer for Zn biofortification was also reported in common beans [113][114][115] and field peas [102].…”
Section: Foliar Fertilizationmentioning
confidence: 99%